High-entropy heat progeny ceramic composite sintering carrier and preparation method thereof

By optimizing components and preparation processes, using high-entropy heat-only ceramic composite sintering carriers, the problems of poor thermal homogenization, poor density, deformation resistance and cracking resistance during high-temperature sintering are solved, and the performance and stability of traditional ceramic materials are significantly improved.

CN119899023AActive Publication Date: 2025-04-29苏州芯合半导体材料有限公司
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510066769.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-29
Estimated Expiration
2045-01-16

AI Technical Summary

Technical Problem

Traditional ceramic materials have problems such as poor thermal homogeneity, poor density, deformation resistance and cracking resistance during high-temperature sintering, which limits their application in extreme environments.

Method used

Using high-entropy thermal quantized ceramic composite sintering carrier, through the optimization of components and preparation processes, including the combination of Al2O3, Si3N4, Yb2O3 doped Y2O3, Y2Si2O7 doped Y3Al5O12 and MgO nanocrystals, combined with technical means such as frozen vacuum in-situ curing, supercritical drying, thermal isostatic sintering, quantum regulation and high-entropy permeability.

Benefits of technology

The performance and stability of high-entropy thermal quantized ceramic composite sintering carrier is significantly improved, and the problems of poor thermal homogenization, poor density, deformation resistance and cracking resistance are solved, and its thermal conductivity, density and mechanical properties in high-temperature environments are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005244487520000251
    Figure BDA0005244487520000251
Patent Text Reader

Abstract

The invention provides a high-entropy heat protonation ceramic composite sintering carrier and a preparation method thereof. The high-entropy heat protonation ceramic composite sintering carrier comprises the following components in percentage by weight: 35-45% of Al2O3 nanocrystal grains; 20% to 30% of Si3N4 nano crystal grains; the content of the Yb2O3 doped Y2O3 nanocrystal grains is 10%-20%; the content of the Y2Si2O7 doped Y3Al 5O12 nanocrystal grains is 15%-25%; 2%-6% of MgO nano crystal grains; by optimizing the components and the preparation process, the technical problems that in the high-temperature sintering process, the soaking property is poor, the compactness is poor, the deformation resistance and the explosion resistance are reduced and the like are solved, and the performance and the stability of the high-entropy heat progenitalization ceramic composite sintering carrier are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic sintered carriers, and in particular to a high-entropy thermal quantized ceramic composite sintered carrier and a preparation method thereof. Background Art

[0002] In the field of advanced materials science, especially in the research and application of ceramic materials, the concept of high entropy materials is gradually showing its great potential. High entropy materials, with their multi-component and high disorder characteristics, usually show better performance than traditional single-component or two-component materials, such as higher hardness, better thermal stability, better wear resistance and corrosion resistance. These characteristics make high entropy materials have a wider range of application prospects in extreme environments, such as high temperature, high pressure, strong radiation and other conditions.

[0003] Ceramic materials, especially those used in precision manufacturing and high-temperature environments, such as splitters in semiconductor packaging, have extremely high requirements for hardness, toughness, and wear resistance. Although traditional ceramic materials can meet these requirements to a certain extent, their performance is often limited when faced with more extreme conditions of use. Therefore, the development of new high-performance ceramic materials has become an important direction of current material science research.

[0004] In recent years, the research on high entropy ceramics has gradually emerged. By introducing the concept of high entropy into the design of ceramic materials, researchers have successfully prepared a series of high entropy ceramics with excellent performance. These high entropy ceramics usually contain multiple main elements, and through fine composition control and preparation process optimization, the material performance can be significantly improved.

[0005] Although high-entropy ceramics have many advantages, they face a series of severe technical challenges during their preparation, especially during the high-temperature sintering stage (temperature is usually ≥1800°C):

[0006] 1. Poor thermal uniformity: Due to the complex composition of high entropy ceramics, the thermal conductivity of different elements varies significantly, making it difficult to achieve uniform heat distribution during the sintering process. This not only affects the uniformity of the microstructure of the material, but may also cause local overheating or uneven cooling, thus affecting the overall performance of the material.

[0007] 2. Poor density: During the high-temperature sintering process, the presence of pores and defects and the uneven growth of grains make it difficult for high-entropy ceramics to achieve an ideal densification level. This will not only reduce the mechanical properties of the material, such as strength and hardness, but may also affect the thermal and chemical stability of the material.

[0008] 3. Decreased deformation resistance and crack resistance: Due to the thermal stress and residual stress generated during the sintering process, as well as the inhomogeneity of the internal microstructure of the material, high-entropy ceramics are prone to deformation or even cracking when subjected to external forces or temperature changes. This not only affects the reliability and stability of the material, but also limits its application in extreme environments.

[0009] The disclosure of the above background technology content is only used to assist in understanding the inventive concept and technical solution of the present invention. It does not necessarily belong to the prior art of this patent application, nor does it necessarily provide technical guidance. In the absence of clear evidence that the above content has been disclosed before the filing date of this patent application, the above background technology should not be used to evaluate the novelty and creativity of the present application. Summary of the invention

[0010] In order to solve the technical problems of poor thermal uniformity, poor density, decreased deformation resistance and anti-blasting rate of traditional sintered carriers, the present invention proposes a high-entropy thermal quantized ceramic composite sintered carrier and a preparation method thereof. By optimizing the components and the preparation process, the technical problems of poor thermal uniformity, poor density, decreased deformation resistance and anti-blasting rate occurring during high-temperature sintering are solved, and the performance and stability of the high-entropy thermal quantized ceramic composite sintered carrier are improved.

[0011] In order to achieve the above object, the technical solution of the present invention is as follows:

[0012] In one aspect, the present invention provides a high entropy thermal quantum ceramic composite sintered carrier, comprising the following components in weight percentage:

[0013] Al 2 O 3 Nanocrystalline particles: 35% to 45%;

[0014] Si 3 N 4 Nanocrystalline particles: 20% to 30%;

[0015] Yb 2 O 3 Doped Y 2 O 3 Nano-crystals: 10% to 20%;

[0016] Y 2 Si 2 O 7 Doped Y 3 Al 5 O 12 Nano-grains: 15% to 25%;

[0017] MgO nanocrystals: 2%~6%.

[0018] The present invention proposes a high-entropy thermal quantized ceramic composite sintered carrier and a preparation method thereof. By optimizing the components and the preparation process, the technical problems such as poor thermal uniformity, poor density, decreased deformation resistance and anti-explosion rate occurring during high-temperature sintering are solved, and the performance and stability of the high-entropy thermal quantized ceramic composite sintered carrier are improved.

[0019] As a preferred technical solution, in the Yb 2 O 3 Doped Y 2 O 3 In the nanocrystals, Yb 2 O 3 The doping amount is 0.1% to 20%.

[0020] As a preferred technical solution, in the Y 2 S i 2 O 7 Doped Y 3 A l 5 O 12 In the nanocrystals, Y 2 S i 2 O 7 The doping amount is 10% to 50%.

[0021] As a preferred technical solution, the Al 2 O 3 Nanocrystalline particles, the Si 3 N 4 Nanocrystalline particles, the Yb 2 O 3 Doped Y 2 O 3 The nanocrystals, the Y 2 Si 2 O 7 Doped Y 3 Al 5 O 12 The particle sizes of the nano-crystals and the MgO nano-crystals are both 5 to 20 nm; 2 O 3 Nanocrystalline particles, the Si 3 N 4 Nanocrystalline particles, the Yb 2 O 3 Doped Y 2 O 3 The nanocrystals, the Y 2 S i 2 O 7 Doped Y 3 Al 5 O 12 The specific surface area of ​​the nano-crystals and the MgO nano-crystals is >50m 2 / g.

[0022] On the other hand, the present invention provides a method for preparing a high entropy thermal quantized ceramic composite sintered carrier, and preparing the high entropy thermal quantized ceramic composite sintered carrier as described in any one of the above items, comprising the following steps:

[0023] S1 weighs Al according to weight percentage 2 O 3 Nanocrystalline particles, Si 3 N 4 Nanocrystals, Yb 2 O 3 Doped Y 2 O 3 Nanocrystals, Y 2 Si 2 O 7 Doped Y 3 Al 5 O 12 The nano-crystals and MgO nano-crystals are ball-milled to obtain a uniformly mixed slurry;

[0024] S2: performing in-situ freeze-vacuum solidification molding on the uniformly mixed slurry to obtain a porous ceramic pre-prestressed body;

[0025] S3 sequentially supercritically drying and pre-sintering the porous ceramic preform to obtain an initial porous ceramic body;

[0026] S4 hot isostatic pressing the initial porous ceramic body to obtain a dense sintered carrier blank;

[0027] S5 sequentially performs quantum control and high entropy infiltration on the dense sintered carrier blank to obtain a high entropy thermal quantum ceramic composite sintered carrier.

[0028] As a preferred technical solution, in step S1, Al is weighed according to weight percentage. 2 O 3 Nanocrystalline particles, Si 3 N 4 Nanocrystals, Yb 2 O 3 Doped Y 2 O 3 Nanocrystals, Y 2 Si 2 O 7 Doped Y 3 A l 5 O 12 The nano-crystals and MgO nano-crystals are ball-milled and mixed, which specifically includes the following steps:

[0029] S101 weighs 35% to 45% Al 2 O3 Nanocrystalline particles, 20% to 30% Si 3 N 4 Nanocrystalline particles, 10% to 20% Yb 2 O 3 Doped Y 2 O 3 Nano-crystals, 15% to 25% Y 2 S i 2 O 7 Doped Y 3 Al 5 O 12 The nano-crystals and 2% to 6% MgO nano-crystals are fed into a ball mill, and then the nano-ZrO 2 The ball is put into the ball mill, and the nano ZrO 2 The weight ratio of the balls to the feedstock is 10:1;

[0030] S102 was ball milled at a speed of 750-850 rpm for 5-7 hours under vacuum argon protection;

[0031] S103: adding dispersant and pore-forming agent, and continuing ball milling for 1.5 to 2.5 hours to obtain a uniformly mixed slurry, wherein the weight ratio of the dispersant to the pore-forming agent is 1:1.

[0032] As a preferred technical solution, step S2 is to freeze-vacuum in-situ solidify the mixed slurry, which specifically includes the following steps:

[0033] S201 injects the uniformly mixed slurry into a prefabricated mold and rapidly freezes it at a temperature of -190 to -170°C to obtain a frozen slurry;

[0034] S202: transferring the frozen slurry to a vacuum in-situ curing device, curing and molding at a temperature of -70 to -50°C for 23 to 24 hours to obtain a porous ceramic pre-prestressed body.

[0035] As a preferred technical solution, step S3 sequentially performs supercritical drying and pre-sintering on the porous ceramic pre-embedded body, which specifically includes the following steps:

[0036] S301 supercritical drying includes the following steps: the porous ceramic pre-existing body is dried by supercritical CO 2 Drying to obtain a dried porous ceramic pre-fixed body;

[0037] S302 pre-sintering includes the following steps: pre-sintering the dried porous ceramic pre-preserved body at a temperature of 750° C. to 850° C. for 1.5 to 2.5 hours to obtain an initial porous ceramic body.

[0038] As a preferred technical solution, step S4 is to perform hot isostatic pressing sintering on the initial porous ceramic body, which specifically includes the following steps:

[0039] S401: The initial porous ceramic body is placed in the hot pressing chamber of the hot pressing machine, and the vacuum degree in the hot pressing chamber is 10 -3 Pa, heated to 1500-1700° C., applied uniaxial pressure of 90-110 MPa, and kept warm for 3.5-4.5 hours to prepare a dense sintered carrier blank.

[0040] As a preferred technical solution, step S5 sequentially performs quantum control and high entropy penetration on the dense sintered carrier blank, specifically comprising the following steps:

[0041] S501 Quantum Control: Densely sintered carrier blanks are placed in a vacuum for 10 -3 Under the Pa state, at a temperature of 850 to 950°C, the temperature is kept for 1.5 to 2.5 hours, the thermal oscillator is quantum controlled, and the temperature is cooled to 200°C to obtain a quantum controlled sintered carrier;

[0042] S502 High Entropy Infiltration: Infiltrate MgO nanopowder into the quantum controlled sintered carrier at a temperature of 1800℃~2000℃, cool it to room temperature, and obtain a high entropy thermal quantum ceramic composite sintered carrier.

[0043] The invention provides a high entropy thermal quantized ceramic composite sintered carrier and a preparation method thereof, which has the following beneficial effects:

[0044] 1) By optimizing the components and preparation process, the technical problems such as poor thermal uniformity, poor density, decreased deformation resistance and anti-explosion rate during high-temperature sintering are solved, and the performance and stability of high-entropy thermal quantum ceramic composite sintering carrier are improved;

[0045] 2) Under high temperature sintering of ≥1800℃, Al 2 O 3 and Si 3 N 4 The reaction between them generates a liquid phase; the presence of the liquid phase can promote Si 3 N 4 The liquid phase can also fill the gaps between the grains, improving the density and strength of the composite ceramics. During the sintering process, sintering aids (such as MgO, Y 2 O 3 etc.) and Al 2 O 3 and Si 3 N 4The reaction generates an intercrystalline glass phase; the intercrystalline glass phase can soften and fill the gaps between the grains at high temperatures, further improving the density of the composite ceramic; at the same time, the intercrystalline glass phase can also play a lubricating role, promoting the rearrangement and densification of the grains; at high temperatures, Si 3 N 4 Solid solution reaction and crystal transformation may occur to generate new crystal phases such as SiAlON; these new crystal phases may have higher hardness and strength, thereby improving the performance of the ceramic composite sintered carrier; solid solution reaction and crystal transformation can also promote the growth and densification of grains, further enhancing the network structure of the ceramic composite sintered carrier; when Al 2 O 3 When the weight percentage of nanocrystals in the component is too low, Al 2 O 3 As a network former, when its content is insufficient, it cannot form a complete network structure; this will lead to 3 N 4 The connection between particles is not tight enough, resulting in more gaps and defects; the incomplete network structure will reduce the high temperature stability of the ceramic composite sintering carrier; at high temperatures, due to the lack of sufficient Al 2 O 3 To stabilize the structure, the ceramic composite sintered carrier may soften, deform or even crack and may not be able to withstand the Si 3 N 4 The formation of a sufficient composite ceramic network structure leads to insufficient structural stability at high temperatures. 2 O 3 When the weight percentage of nanoparticles in the component is too high, too much Al 2 O 3 The content may occupy too much space, making Si 3 N 4 It is difficult for sandwich clusters to form between particles. The formation of sandwich clusters helps to transfer and disperse heat in the ceramic composite sintered carrier. When the formation of sandwich clusters is blocked, the thermal quantization effect will be weakened, resulting in a decrease in the thermal conductivity of the ceramic composite sintered carrier. Therefore, the present application Al 2 O 3 The content of nano-crystals in the ceramic composite sintering carrier needs to be controlled within an appropriate range (such as 35% to 45%) to ensure that the nano-crystals are compatible with Si. 3 N 4 Forming a sufficient composite ceramic network structure, so that the structure is not stable enough at high temperature, and at the same time improving the thermal conductivity of the ceramic composite sintered carrier;

[0046] Yb is added to the components of this application 2 O 3 Doped Y 2 O 3Nanocrystals of rare earth oxides. The rare earth elements in rare earth oxides have a unique 4f electron layer structure. These electrons will produce rich spectral properties when they jump between energy levels. 2 O 3 Doped Y 2 O 3 In the nanocrystals, Yb 3+ The 4f electrons of the ions may interact with the 4f electrons of other rare earth elements or other electrons in the lattice, thereby enhancing the coupling between quantum states; the enhancement of quantum state coupling helps electrons to transition between energy levels more efficiently, which may promote heat transfer in smaller units (i.e., closer to quantum form) and promote the heat quantization process. Heat quantization helps heat to be more evenly distributed inside the material, thereby improving thermal uniformity;

[0047] This application 2 O 3 Doped Y 2 O 3 The weight percentage of nano-crystals in the component is preferably 10% to 20%, and an appropriate amount of Yb 2 O 3 Doping can refine Y 2 O 3 The grain size of Yb is small, and the small grains can be arranged more closely together, reducing the gaps between the grains, thereby improving the density of the material. 2 O 3 As a dopant, Y 2 O 3 Tiny pores and defects in the matrix; this filling effect helps to reduce the porosity of the material and further improve the density; Yb 2 O 3 Doped Y 2 O 3 The weight percentage of nano-grains is 10% to 20%, which reduces the overall density of the material, thereby improving the material's resistance to deformation and explosion;

[0048] Y 2 Si 2 O 7 Doped Y 3 A l 5 O 12 Nanocrystals: 15% to 25%, Y 2 Si 2 O 7 The doping can be 3 Al 5 O 12The formation of nano-grains at the grain boundaries can optimize the grain boundary structure and reduce defects and scattering centers at the grain boundaries; the optimized grain boundary structure helps heat to be transferred more efficiently between grains, reducing heat loss and scattering at the grain boundaries, thereby improving the overall heat transfer rate; Y 2 S i 2 O 7 Doped Y 3 Al 5 O 12 The weight percentage of nano-crystals is preferably 15% to 25%, and an appropriate amount of Y 2 Si 2 O 7 Doping can form continuous heat conduction paths that can more efficiently transfer heat from one part of the material to another. This continuous heat conduction path helps reduce the diffusion resistance of heat inside the material, further improving the thermal conductivity of the material, which also helps to achieve a more uniform heat distribution, thereby improving thermal uniformity.

[0049] Y 2 Si 2 O 7 The doping can fill Y 3 Al 5 O 12 The voids and pores in the material reduce the porosity of the material; the filling effect helps to increase the density of the material, making the material more compact and strong; 2 Si 2 O 7 Doped Y 3 Al 5 O 12 The weight percentage of nano-crystals is preferably 15% to 25%, and an appropriate amount of Y 2 Si 2 O 7 Doping can inhibit Y 3 Al 5 O 12 The excessive growth of grains makes the grain size more uniform and fine; the uniform grain size helps to further improve the density of the material;

[0050] Y 2 Si 2 O 7 Doping enhanced Y 3 Al 5 O 12 Strength at grain boundaries; strengthened grain boundaries can more effectively resist external stress and deformation, thereby improving the material's resistance to deformation.

[0051] The introduction of magnesium oxide nanoparticles enhances the high-temperature atomic diffusion and migration capabilities of the material. This is because nanoparticles have a higher specific surface area and surface activity, which can provide more atomic diffusion channels and migration sites. In addition, the introduction of nanoparticles may also change the grain boundary structure and chemical composition of the material, thereby affecting the diffusion and migration behavior of atoms. At high temperatures, the enhanced diffusion and migration capabilities of atoms contribute to the homogenization and densification process inside the material, thereby improving the overall performance of the material.

[0052] The weight percentage of magnesium oxide nanoparticles is preferably 2% to 6%. Optimizing the ratio of magnesium oxide nanoparticles can inhibit the deformation and cracking of the material to a certain extent, because the introduction of magnesium oxide nanoparticles can change the mechanical properties of the material, such as improving the grain boundary strength; these changes help reduce defects and stress concentration inside the material, thereby improving the material's ability to resist deformation and cracking. In addition, the introduction of magnesium oxide nanoparticles may also change the thermal expansion coefficient and thermal stress distribution of the material, thereby helping to reduce thermal stress concentration and cracking caused by temperature changes.

[0053] 3) The high-entropy thermal quantized ceramic composite sintered carrier provided by the present invention significantly improves the comprehensive performance of the material by introducing a variety of nano-crystals and doped nano-crystals during the preparation process, and adopts high entropy effect and quantum control technology and processes. It not only realizes the thermal quantized transfer of the sintered carrier, but also has excellent high-temperature performance with high entropy stability, improves the thermal conduction efficiency, high-temperature stability and mechanical properties of the sintered carrier, and is not prone to technical problems such as severe deformation or cracking. DETAILED DESCRIPTION

[0054] The preferred embodiments of the present invention are described in detail below with reference to the embodiments.

[0055] The present invention provides a high entropy thermal quantum ceramic composite sintered carrier, comprising the following components in weight percentage:

[0056] Al 2 O 3 Nanocrystalline particles: 35% to 45%;

[0057] Si 3 N 4 Nanocrystalline particles: 20% to 30%;

[0058] Yb 2 O 3 Doped Y 2 O 3 Nano-crystals: 10% to 20%;

[0059] Y 2 Si 2 O 7 Doped Y 3 Al5 O 12 Nano-grains: 15% to 25%;

[0060] MgO nanocrystals: 2%~6%.

[0061] The present invention proposes a high-entropy thermal quantized ceramic composite sintered carrier, which improves the thermal conductivity, high-temperature stability and mechanical properties of the sintered carrier, solves the shortcomings of traditional sintered carriers in the high-entropy ceramic sintering process, and ensures the quality of the sintered carrier and the performance of the final product.

[0062] Preferably, in the Yb 2 O 3 Doped Y 2 O 3 In the nanocrystals, Yb 2 O 3 The doping amount of Yb is 0.1% to 20%; 2 O 3 The doping amount is preferably 0.1%, 0.6%, 1%, 5%, 10%, 15% and 20%. Due to the limited space and for the sake of simplicity, the present invention will no longer exhaustively list the specific point values ​​included in the range;

[0063] Preferably, in the Y 2 Si 2 O 7 Doped Y 3 A l 5 O 12 In the nanocrystals, Y 2 Si 2 O 7 The doping amount of Y is 10% to 50%. 2 Si 2 O 7 The doping amount is preferably 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45% and 50%. Due to the limited space and for the sake of simplicity, the present invention will no longer exhaustively list the specific point values ​​included in the range;

[0064] Preferably, the A1 2 O 3 Nanocrystalline particles, the Si 3 N 4 Nanocrystalline particles, the Yb 2 O 3 Doped Y 2 O 3 The nanocrystals, the Y 2 S i 2 O 7 Doped Y 3 Al 5 O 12The particle sizes of the nano-crystals and the MgO nano-crystals are both 5 to 20 nm; 2 O 3 Nanocrystalline particles, the Si 3 N 4 Nanocrystalline particles, the Yb 2 O 3 Doped Y 2 O 3 The nanocrystals, the Y 2 S i 2 O 7 Doped Y 3 Al 5 O 12 The particle sizes of the nano-crystals and the MgO nano-crystals are preferably 5 nm, 10 nm, 15 nm and 20 nm. Due to space limitations and for the sake of simplicity, the present invention will no longer exhaustively list the specific point values ​​included in the range; the Al 2 O 3 Nanocrystalline particles, the Si 3 N 4 Nanocrystalline particles, the Yb 2 O 3 Doped Y 2 O 3 The nanocrystals, the Y 2 S i 2 O 7 Doped Y 3 A l 5 O 12 The specific surface area of ​​the nano-crystals and the MgO nano-crystals is >50m 2 / g.

[0065] The present invention provides a method for preparing a high entropy thermal quantized ceramic composite sintered carrier, and the method comprises the following steps:

[0066] S1 weighs Al according to weight percentage 2 O 3 Nanocrystalline particles, Si 3 N 4 Nanocrystals, Yb 2 O 3 Doped Y 2 O 3 Nanocrystals, Y 2 Si 2 O 7 Doped Y 3 Al 5 O 12 The nano-crystals and MgO nano-crystals are ball-milled to obtain a uniformly mixed slurry, which specifically includes the following steps:

[0067] S101 weighs 35% to 45% Al 2 O 3 Nanocrystalline particles, 20% to 30% Si 3 N 4 Nanocrystalline particles, 10% to 20% Yb 2 O 3 Doped Y 2 O 3 Nano-crystals, 15% to 25% Y 2 S i 2 O 7 Doped Y 3 Al 5 O 12 The nano-crystals and 2% to 6% MgO nano-crystals are fed into a ball mill, and then the nano-ZrO 2 The ball is put into the ball mill, and the nano ZrO 2 The weight ratio of the balls to the feedstock is 10:1;

[0068] S102 was ball milled at a speed of 750-850 rpm for 5-7 hours under vacuum argon protection;

[0069] S103: adding a dispersant and a pore-forming agent, and continuing ball milling for 1.5 to 2.5 hours to obtain a uniformly mixed slurry, wherein the weight ratio of the dispersant to the pore-forming agent is 1:1;

[0070] S2 is to freeze-vacuum in-situ solidify the uniformly mixed slurry to obtain a porous ceramic pre-prestressed body, which specifically includes the following steps:

[0071] S201 injects the uniformly mixed slurry into a prefabricated mold and rapidly freezes it at a temperature of -190 to -170°C to obtain a frozen slurry;

[0072] S202: transferring the frozen slurry to a vacuum in-situ curing device, curing and molding at a temperature of -70 to -50°C for 23 to 24 hours to obtain a porous ceramic pre-prestressed body;

[0073] S3 sequentially performs supercritical drying and pre-sintering on the porous ceramic pre-existing body to obtain an initial porous ceramic body, which specifically includes the following steps:

[0074] S301 supercritical drying includes the following steps: the porous ceramic pre-existing body is dried by supercritical CO 2 Drying to obtain a dried porous ceramic pre-fixed body;

[0075] S302 pre-sintering, including the following steps: pre-sintering the dried porous ceramic pre-preserved body at a temperature of 750° C. to 850° C. for 1.5 to 2.5 hours to obtain an initial porous ceramic body;

[0076] S4 performs hot isostatic pressing sintering on the initial porous ceramic body to obtain a dense sintered carrier blank, which specifically includes the following steps:

[0077] S401: The initial porous ceramic body is placed in the hot pressing chamber of the hot pressing machine, and the vacuum degree in the hot pressing chamber is 10 -3 Pa, heated to 1500-1700°C, applied uniaxial pressure of 90-110 MPa, and kept warm for 3.5-4.5 hours to prepare a dense sintered carrier blank;

[0078] S5 sequentially performs quantum control and high entropy infiltration on the dense sintered carrier blank to obtain a high entropy thermal quantum ceramic composite sintered carrier, which specifically includes the following steps:

[0079] S501 Quantum Control: Densely sintered carrier blanks are placed in a vacuum for 10 -3 In the Pa state, the temperature is kept at 850-950°C for 1.5-2.5 hours, the thermal oscillator is quantum controlled, and the temperature is cooled to 200°C to obtain a quantum controlled sintered carrier;

[0080] S502 High Entropy Infiltration: Infiltrate MgO nanopowder into the quantum controlled sintered carrier at a temperature of 1800℃~2000℃, cool it to room temperature, and obtain a high entropy thermal quantum ceramic composite sintered carrier.

[0081] The present invention provides a method for preparing a high-entropy thermal quantized ceramic composite sintered carrier. During the preparation process of the high-entropy thermal quantized ceramic composite sintered carrier, a variety of nano-crystals and doped nano-crystals are introduced, and high entropy effect and quantum control technology and process are adopted, thereby significantly improving the comprehensive performance of the material, not only realizing the quantized transfer of heat of the sintered carrier, but also having excellent high-temperature performance of high entropy stability, improving the thermal conduction efficiency, high-temperature stability and mechanical properties of the sintered carrier, and not being prone to technical problems such as severe deformation or cracking.

[0082] Example 1

[0083] The present invention provides a method for preparing a high entropy thermal quantized ceramic composite sintered carrier, comprising the following steps:

[0084] S1 weighs Al according to weight percentage 2 O 3 Nanocrystalline particles, Si 3 N 4 Nanocrystals, Yb 2 O 3 Doped Y 2 O 3 Nanocrystals, Y 2 Si 2 O 7 Doped Y 3 Al5 O 12 The nano-crystals and MgO nano-crystals are ball-milled to obtain a uniformly mixed slurry, which specifically includes the following steps:

[0085] S101 weighs 38% A l 2 O 3 Nanocrystalline, 23% Si 3 N 4 Nanocrystalline, 15% Yb 2 O 3 Doped Y 2 O 3 Nanocrystals, 20% Y 2 S i 2 O 7 Doped Y 3 A l 5 O 12 The nano-crystals and 4% MgO nano-crystals are fed into a ball mill, and then the nano-ZrO2 balls are put into the ball mill, wherein the weight ratio of the nano-ZrO2 balls to the feed is 10:1;

[0086] S102 was ball milled at 800 rpm for 6 hours under vacuum argon protection;

[0087] S103: adding a dispersant and a pore-forming agent, and continuing ball milling for 2 hours to obtain a uniformly mixed slurry, wherein the weight ratio of the dispersant to the pore-forming agent is 1:1;

[0088] S2 is to freeze-vacuum in-situ solidify the uniformly mixed slurry to obtain a porous ceramic pre-prestressed body, which specifically includes the following steps:

[0089] S201 injects the uniformly mixed slurry into a prefabricated mold and rapidly freezes it at -180°C to obtain a frozen slurry;

[0090] S202: transferring the frozen slurry to a vacuum in-situ curing device, curing and molding at -60°C for 23.5 hours to obtain a porous ceramic pre-prestressed body;

[0091] S3 sequentially performs supercritical drying and pre-sintering on the porous ceramic pre-existing body to obtain an initial porous ceramic body, which specifically includes the following steps:

[0092] S301 supercritical drying includes the following steps: the porous ceramic pre-existing body is dried by supercritical CO 2 Drying to obtain a dried porous ceramic pre-fixed body;

[0093] S302 pre-sintering, including the following steps: pre-sintering the dried porous ceramic pre-preserved body at 800° C. for 2 hours to obtain an initial porous ceramic body;

[0094] S4 performs hot isostatic pressing sintering on the initial porous ceramic body to obtain a dense sintered carrier blank, which specifically includes the following steps:

[0095] S401: The initial porous ceramic body is placed in the hot pressing chamber of the hot pressing machine, and the vacuum degree in the hot pressing chamber is 10 -3 Pa, heated to 1600°C, applied uniaxial pressure of 100 MPa, and kept warm for 4 hours to prepare a dense sintered carrier blank;

[0096] S5 sequentially performs quantum control and high entropy infiltration on the dense sintered carrier blank to obtain a high entropy thermal quantum ceramic composite sintered carrier, which specifically includes the following steps:

[0097] S501 Quantum Control: Densely sintered carrier blanks are placed in a vacuum for 10 -3 In the Pa state, the temperature was kept at 900°C for 2 hours, the thermal oscillator was quantum controlled, and then cooled to 200°C to obtain a quantum controlled sintered carrier;

[0098] S502 High Entropy Infiltration: Infiltrate MgO nanopowder into the quantum controlled sintered carrier at 1800°C, cool it to room temperature, and obtain a high entropy thermal quantum ceramic composite sintered carrier.

[0099] Example 2

[0100] The present invention provides a method for preparing a high entropy thermal quantized ceramic composite sintered carrier, comprising the following steps:

[0101] S1 weighs Al according to weight percentage 2 O 3 Nanocrystalline particles, Si 3 N 4 Nanocrystals, Yb 2 O 3 Doped Y 2 O 3 Nanocrystals, Y 2 Si 2 O 7 Doped Y 3 Al 5 O 12 The nano-crystals and MgO nano-crystals are ball-milled to obtain a uniformly mixed slurry, which specifically includes the following steps:

[0102] S101 weighs 35% Al 2 O 3 Nanocrystalline, 30% Si 3 N 4 Nanocrystalline, 18% Yb 2 O 3 Doped Y 2O 3 Nano-crystals, 15% Y 2 S i 2 O 7 Doped Y 3 A l 5 O 12 The nano-crystals and 2% MgO nano-crystals were fed into a ball mill, and then the nano-ZrO 2 The ball is put into the ball mill, and the nano ZrO 2 The weight ratio of the balls to the feedstock is 10:1;

[0103] S102 was ball milled at 750 rpm for 7 hours under vacuum argon protection;

[0104] S103: adding a dispersant and a pore-forming agent, and continuing ball milling for 1.5 hours to obtain a uniformly mixed slurry, wherein the weight ratio of the dispersant to the pore-forming agent is 1:1;

[0105] S2 is to freeze-vacuum in-situ solidify the uniformly mixed slurry to obtain a porous ceramic pre-prestressed body, which specifically includes the following steps:

[0106] S201 injects the uniformly mixed slurry into a prefabricated mold, and rapidly freezes it at -190°C to obtain a frozen slurry;

[0107] S202: transferring the frozen slurry to a vacuum in-situ curing device, curing and molding at -70°C for 23 hours to obtain a porous ceramic pre-prestressed body;

[0108] S3 sequentially supercritically dries and pre-sinters the porous ceramic pre-existing body to obtain an initial porous ceramic body, which specifically includes the following steps:

[0109] S301 supercritical drying includes the following steps: the porous ceramic pre-existing body is dried by supercritical CO 2 Drying to obtain a dried porous ceramic pre-fixed body;

[0110] S302 pre-sintering, including the following steps: pre-sintering the dried porous ceramic pre-preserved body at 750° C. for 2.5 hours to obtain an initial porous ceramic body;

[0111] S4 performs hot isostatic pressing sintering on the initial porous ceramic body to obtain a dense sintered carrier blank, which specifically includes the following steps:

[0112] S401: The initial porous ceramic body is placed in the hot pressing chamber of the hot pressing machine, and the vacuum degree in the hot pressing chamber is 10 -3 Pa, heated to 1500°C, applied uniaxial pressure of 110 MPa, and kept warm for 4.5 hours to prepare a dense sintered carrier blank;

[0113] S5 sequentially performs quantum control and high entropy infiltration on the dense sintered carrier blank to obtain a high entropy thermal quantum ceramic composite sintered carrier, which specifically includes the following steps:

[0114] S501 Quantum Control: Densely sintered carrier blanks are placed in a vacuum for 10 -3 Under the Pa state, the temperature was kept at 850°C for 2.5 hours, the thermal oscillator was quantum controlled, and then cooled to 200°C to obtain a quantum controlled sintered carrier;

[0115] S502 High Entropy Infiltration: Infiltrate MgO nanopowder into the quantum controlled sintered carrier at 1900°C, cool it to room temperature, and obtain a high entropy thermal quantum ceramic composite sintered carrier.

[0116] Example 3

[0117] The present invention provides a method for preparing a high entropy thermal quantized ceramic composite sintered carrier, comprising the following steps:

[0118] S1 weighs Al according to weight percentage 2 O 3 Nanocrystalline particles, Si 3 N 4 Nanocrystals, Yb 2 O 3 Doped Y 2 O 3 Nanocrystals, Y 2 Si 2 O 7 Doped Y 3 Al 5 O 12 The nano-crystals and MgO nano-crystals are ball-milled to obtain a uniformly mixed slurry, which specifically includes the following steps:

[0119] S101 weighs 45% Al 2 O 3 Nanocrystalline, 20% Si 3 N 4 Nanocrystalline, 12% Yb 2 O 3 Doped Y 2 O 3 Nano-crystals, 17% Y 2 Si 2 O 7 Doped Y 3 Al 5 O 12 The nano-crystals and 6% MgO nano-crystals were fed into a ball mill, and then the nano-ZrO 2 The ball is put into the ball mill, and the nano ZrO 2 The weight ratio of the balls to the feedstock is 10:1;

[0120] S102 was ball milled at 850 rpm for 5 hours under vacuum argon protection;

[0121] S103: adding a dispersant and a pore-forming agent, and continuing ball milling for 2.5 hours to obtain a uniformly mixed slurry, wherein the weight ratio of the dispersant to the pore-forming agent is 1:1;

[0122] S2 is to freeze-vacuum in-situ solidify the uniformly mixed slurry to obtain a porous ceramic pre-prestressed body, which specifically includes the following steps:

[0123] S201 injects the uniformly mixed slurry into a prefabricated mold, and rapidly freezes it at -170°C to obtain a frozen slurry;

[0124] S202: transferring the frozen slurry to a vacuum in-situ curing device, curing and molding at -50°C for 24 hours to obtain a porous ceramic pre-prestressed body;

[0125] S3 sequentially supercritically dries and pre-sinters the porous ceramic pre-existing body to obtain an initial porous ceramic body, which specifically includes the following steps:

[0126] S301 supercritical drying includes the following steps: the porous ceramic pre-existing body is dried by supercritical CO 2 Drying to obtain a dried porous ceramic pre-fixed body;

[0127] S302 pre-sintering, including the following steps: pre-sintering the dried porous ceramic pre-preserved body at 850° C. for 1.5 hours to obtain an initial porous ceramic body;

[0128] S4 performs hot isostatic pressing sintering on the initial porous ceramic body to obtain a dense sintered carrier blank, which specifically includes the following steps:

[0129] S401: The initial porous ceramic body is placed in the hot pressing chamber of the hot pressing machine, and the vacuum degree in the hot pressing chamber is 10 -3 Pa, heated to 1700°C, applied uniaxial pressure of 90MPa, and kept warm for 3.5 hours to prepare a dense sintered carrier blank;

[0130] S5 sequentially performs quantum control and high entropy infiltration on the dense sintered carrier blank to obtain a high entropy thermal quantum ceramic composite sintered carrier, which specifically includes the following steps:

[0131] S501 Quantum Control: Densely sintered carrier blanks are placed in a vacuum for 10 -3 Under the Pa state, the temperature was kept at 950°C for 1.5 hours, the thermal oscillator was quantum controlled, and then cooled to 200°C to obtain a quantum controlled sintered carrier;

[0132] S502 High Entropy Infiltration: Infiltrate MgO nanopowder into the quantum controlled sintered carrier at 2000°C, cool it to room temperature, and obtain a high entropy thermal quantum ceramic composite sintered carrier.

[0133] Comparative Example 1

[0134] Comparative Example 1 provides a method for preparing a high entropy thermal quantized ceramic composite sintered carrier, comprising the following steps:

[0135] S1 weighs Al according to weight percentage 2 O 3 Nanocrystalline particles, Si 3 N 4 Nanocrystals, Yb 2 O 3 Doped Y 2 O 3 Nanocrystals, Y 2 Si 2 O 7 Doped Y 3 Al 5 O 12 The nano-crystals and MgO nano-crystals are ball-milled to obtain a uniformly mixed slurry, which specifically includes the following steps:

[0136] S101 weighs 30% Al 2 O 3 Nanocrystalline, 25% Si 3 N 4 Nanocrystalline, 20% Yb 2 O 3 Doped Y 2 O 3 Nano-crystals, 21% Y 2 S i 2 O 7 Doped Y 3 A l 5 O 12 The nano-crystals and 4% MgO nano-crystals were fed into a ball mill, and then the nano-ZrO 2 The ball is put into the ball mill, and the nano ZrO 2 The weight ratio of the balls to the feedstock is 10:1;

[0137] S102 was ball milled at 800 rpm for 6 hours under vacuum argon protection;

[0138] S103: adding a dispersant and a pore-forming agent, and continuing ball milling for 2 hours to obtain a uniformly mixed slurry, wherein the weight ratio of the dispersant to the pore-forming agent is 1:1;

[0139] S2 is to freeze-vacuum in-situ solidify the uniformly mixed slurry to obtain a porous ceramic pre-prestressed body, which specifically includes the following steps:

[0140] S201 injects the uniformly mixed slurry into a prefabricated mold and rapidly freezes it at -180°C to obtain a frozen slurry;

[0141] S202: transferring the frozen slurry to a vacuum in-situ curing device, curing and molding at -60°C for 23.5 hours to obtain a porous ceramic pre-prestressed body;

[0142] S3 sequentially performs supercritical drying and pre-sintering on the porous ceramic pre-existing body to obtain an initial porous ceramic body, which specifically includes the following steps:

[0143] S301 supercritical drying includes the following steps: the porous ceramic pre-existing body is dried by supercritical CO 2 Drying to obtain a dried porous ceramic pre-fixed body;

[0144] S302 pre-sintering, including the following steps: pre-sintering the dried porous ceramic pre-preserved body at 800° C. for 2 hours to obtain an initial porous ceramic body;

[0145] S4 performs hot isostatic pressing sintering on the initial porous ceramic body to obtain a dense sintered carrier blank, which specifically includes the following steps:

[0146] S401: The initial porous ceramic body is placed in the hot pressing chamber of the hot pressing machine, and the vacuum degree in the hot pressing chamber is 10 -3 Pa, heated to 1600°C, applied uniaxial pressure of 100 MPa, and kept warm for 4 hours to prepare a dense sintered carrier blank;

[0147] S5 sequentially performs quantum control and high entropy infiltration on the dense sintered carrier blank to obtain a high entropy thermal quantum ceramic composite sintered carrier, which specifically includes the following steps:

[0148] S501 Quantum Control: Densely sintered carrier blanks are placed in a vacuum for 10 -3 In the Pa state, the temperature was kept at 900°C for 2 hours, the thermal oscillator was quantum controlled, and then cooled to 200°C to obtain a quantum controlled sintered carrier;

[0149] S502 High Entropy Infiltration: Infiltrate MgO nanopowder into the quantum controlled sintered carrier at 1800°C, cool it to room temperature, and obtain a high entropy thermal quantum ceramic composite sintered carrier.

[0150] Comparative Example 2

[0151] Comparative Example 2 provides a method for preparing a high entropy thermal quantized ceramic composite sintered carrier, comprising the following steps:

[0152] S1 weighs Al according to weight percentage 2 O 3 Nanocrystalline particles, Si 3 N 4 Nanocrystals, Yb 2 O 3 Doped Y 2 O 3 Nanocrystals, Y 2 Si 2 O 7 Doped Y 3 Al 5 O 12 The nano-crystals and MgO nano-crystals are ball-milled to obtain a uniformly mixed slurry, which specifically includes the following steps:

[0153] S101 weighs 50% Al 2 O 3 Nanocrystalline, 20% Si 3 N 4 Nanocrystalline, 10% Yb 2 O 3 Doped Y 2 O 3 Nano-crystals, 15% Y 2 Si 2 O 7 Doped Y 3 Al 5 O 12 The nano-crystals and 5% MgO nano-crystals were fed into a ball mill, and then the nano-ZrO 2 The ball is put into the ball mill, and the nano ZrO 2 The weight ratio of the balls to the feedstock is 10:1;

[0154] S102 was ball milled at 800 rpm for 6 hours under vacuum argon protection;

[0155] S103: adding a dispersant and a pore-forming agent, and continuing ball milling for 2 hours to obtain a uniformly mixed slurry, wherein the weight ratio of the dispersant to the pore-forming agent is 1:1;

[0156] S2 is to freeze-vacuum in-situ solidify the uniformly mixed slurry to obtain a porous ceramic pre-prestressed body, which specifically includes the following steps:

[0157] S201 injects the mixed slurry into the prefabricated mold and quickly freezes it at -180℃.

[0158] obtaining a frozen slurry;

[0159] S202: transferring the frozen slurry to a vacuum in-situ curing device, curing and molding at -60°C for 23.5 hours to obtain a porous ceramic pre-prestressed body;

[0160] S3 sequentially performs supercritical drying and pre-sintering on the porous ceramic pre-existing body to obtain an initial porous ceramic body, which specifically includes the following steps:

[0161] S301 supercritical drying includes the following steps: the porous ceramic pre-existing body is dried by supercritical CO 2 Drying to obtain a dried porous ceramic pre-fixed body;

[0162] S302 pre-sintering, including the following steps: pre-sintering the dried porous ceramic pre-preserved body at 800° C. for 2 hours to obtain an initial porous ceramic body;

[0163] S4 performs hot isostatic pressing sintering on the initial porous ceramic body to obtain a dense sintered carrier blank, which specifically includes the following steps:

[0164] S401: The initial porous ceramic body is placed in the hot pressing chamber of the hot pressing machine, and the vacuum degree in the hot pressing chamber is 10 -3 Pa, heated to 1600°C, applied uniaxial pressure of 100 MPa, and kept warm for 4 hours to prepare a dense sintered carrier blank;

[0165] S5 sequentially performs quantum control and high entropy infiltration on the dense sintered carrier blank to obtain a high entropy thermal quantum ceramic composite sintered carrier, which specifically includes the following steps:

[0166] S501 Quantum Control: Densely sintered carrier blanks are placed in a vacuum for 10 -3 In the Pa state, the temperature was kept at 900°C for 2 hours, the thermal oscillator was quantum controlled, and then cooled to 200°C to obtain a quantum controlled sintered carrier;

[0167] S502 High Entropy Infiltration: Infiltrate MgO nanopowder into the quantum controlled sintered carrier at 1800°C, cool it to room temperature, and obtain a high entropy thermal quantum ceramic composite sintered carrier.

[0168] Comparative Example 3

[0169] Comparative Example 3 provides a method for preparing a high entropy thermal quantized ceramic composite sintered carrier, comprising the following steps:

[0170] S1 weighs Al according to weight percentage 2 O 3 Nanocrystalline particles, Si 3 N 4 Nanocrystals, Yb 2 O 3 Doped Y 2 O 3Nanocrystals, Y 2 Si 2 O 7 Doped Y 3 Al 5 O 12 The nano-crystals and MgO nano-crystals are ball-milled to obtain a uniformly mixed slurry, which specifically includes the following steps:

[0171] S101 weighs 23% Si 3 N 4 Nanocrystalline, 15% Yb 2 O 3 Doped Y 2 O 3 Nanocrystals, 20% Y 2 S i 2 O 7 Doped Y 3 A l 5 O 12 The nano-crystals and 4% MgO nano-crystals were fed into a ball mill, and then the nano-ZrO 2 The ball is put into the ball mill, and the nano ZrO 2 The weight ratio of the balls to the feedstock is 10:1;

[0172] S102 was ball milled at 800 rpm for 6 hours under vacuum argon protection;

[0173] S103: adding a dispersant and a pore-forming agent, and continuing ball milling for 2 hours to obtain a uniformly mixed slurry, wherein the weight ratio of the dispersant to the pore-forming agent is 1:1;

[0174] S2 is to freeze-vacuum in-situ solidify the uniformly mixed slurry to obtain a porous ceramic pre-prestressed body, which specifically includes the following steps:

[0175] S201 injects the uniformly mixed slurry into a prefabricated mold and rapidly freezes it at -180°C to obtain a frozen slurry;

[0176] S202: transferring the frozen slurry to a vacuum in-situ curing device, curing and molding at -60°C for 23.5 hours to obtain a porous ceramic pre-prestressed body;

[0177] S3 sequentially performs supercritical drying and pre-sintering on the porous ceramic pre-existing body to obtain an initial porous ceramic body, which specifically includes the following steps:

[0178] S301 supercritical drying includes the following steps: the porous ceramic pre-existing body is dried by supercritical CO 2 Drying to obtain a dried porous ceramic pre-fixed body;

[0179] S302 pre-sintering, including the following steps: pre-sintering the dried porous ceramic pre-preserved body at 800° C. for 2 hours to obtain an initial porous ceramic body;

[0180] S4 performs hot isostatic pressing sintering on the initial porous ceramic body to obtain a dense sintered carrier blank, which specifically includes the following steps:

[0181] S401: The initial porous ceramic body is placed in the hot pressing chamber of the hot pressing machine, and the vacuum degree in the hot pressing chamber is 10 -3 Pa, heated to 1600°C, applied uniaxial pressure of 100 MPa, and kept warm for 4 hours to prepare a dense sintered carrier blank;

[0182] S5 sequentially performs quantum control and high entropy infiltration on the dense sintered carrier blank to obtain a high entropy thermal quantum ceramic composite sintered carrier, which specifically includes the following steps:

[0183] S501 Quantum Control: Densely sintered carrier blanks are placed in a vacuum for 10 -3 In the Pa state, the temperature was kept at 900°C for 2 hours, the thermal oscillator was quantum controlled, and then cooled to 200°C to obtain a quantum controlled sintered carrier;

[0184] S502 High Entropy Infiltration: Infiltrate MgO nanopowder into the quantum controlled sintered carrier at 1800°C, cool it to room temperature, and obtain a high entropy thermal quantum ceramic composite sintered carrier.

[0185] Comparative Example 4

[0186] Comparative Example 4 provides a method for preparing a high entropy thermal quantized ceramic composite sintered carrier, comprising the following steps:

[0187] S1 weighs Al according to weight percentage 2 O 3 Nanocrystalline particles, Si 3 N 4 Nanocrystals, Yb 2 O 3 Doped Y 2 O 3 Nanocrystals, Y 2 Si 2 O 7 Doped Y 3 Al 5 O 12 The nano-crystals and MgO nano-crystals are ball-milled to obtain a uniformly mixed slurry, which specifically includes the following steps:

[0188] S101 is 38% Al by weight 2 O 3 Nanocrystalline, 23% Si 3 N4 Nanocrystalline, 20% Y 2 S i 2 O 7 Doped Y 3 A l 5 O 12 The nano-crystals and 4% MgO nano-crystals were fed into a ball mill, and then the nano-ZrO 2 The ball is put into the ball mill, and the nano ZrO 2 The weight ratio of the balls to the feedstock is 10:1;

[0189] S102 was ball milled at 800 rpm for 6 hours under vacuum argon protection;

[0190] S103: adding a dispersant and a pore-forming agent, and continuing ball milling for 2 hours to obtain a uniformly mixed slurry, wherein the weight ratio of the dispersant to the pore-forming agent is 1:1;

[0191] S2 is to freeze-vacuum in-situ solidify the uniformly mixed slurry to obtain a porous ceramic pre-prestressed body, which specifically includes the following steps:

[0192] S201 injects the mixed slurry into the prefabricated mold and quickly freezes it at -180℃.

[0193] obtaining a frozen slurry;

[0194] S202: transferring the frozen slurry to a vacuum in-situ curing device, curing and molding at -60°C for 23.5 hours to obtain a porous ceramic pre-prestressed body;

[0195] S3 sequentially supercritically dries and pre-sinters the porous ceramic pre-existing body to obtain an initial porous ceramic body, which specifically includes the following steps:

[0196] S301 supercritical drying includes the following steps: the porous ceramic pre-existing body is dried by supercritical CO 2 Drying to obtain a dried porous ceramic pre-fixed body;

[0197] S302 pre-sintering, including the following steps: pre-sintering the dried porous ceramic pre-preserved body at 800° C. for 2 hours to obtain an initial porous ceramic body;

[0198] S4 performs hot isostatic pressing sintering on the initial porous ceramic body to obtain a dense sintered carrier blank, which specifically includes the following steps:

[0199] S401: The initial porous ceramic body is placed in the hot pressing chamber of the hot pressing machine, and the vacuum degree in the hot pressing chamber is 10 -3 Pa, heated to 1600°C, applied uniaxial pressure of 100 MPa, and kept warm for 4 hours to prepare a dense sintered carrier blank;

[0200] S5 sequentially performs quantum control and high entropy infiltration on the dense sintered carrier blank to obtain a high entropy thermal quantum ceramic composite sintered carrier, which specifically includes the following steps:

[0201] S501 Quantum Control: Densely sintered carrier blanks are placed in a vacuum for 10 -3 In the Pa state, the temperature was kept at 900°C for 2 hours, the thermal oscillator was quantum controlled, and then cooled to 200°C to obtain a quantum controlled sintered carrier;

[0202] S502 High Entropy Infiltration: Infiltrate MgO nanopowder into the quantum controlled sintered carrier at 1800°C, cool it to room temperature, and obtain a high entropy thermal quantum ceramic composite sintered carrier.

[0203] Comparative Example 5

[0204] Comparative Example 5 provides a method for preparing a high entropy thermal quantized ceramic composite sintered carrier, comprising the following steps:

[0205] S1 weighs Al according to weight percentage 2 O 3 Nanocrystalline particles, Si 3 N 4 Nanocrystals, Yb 2 O 3 Doped Y 2 O 3 Nanocrystals, Y 2 Si 2 O 7 Doped Y 3 Al 5 O 12 The nano-crystals and MgO nano-crystals are ball-milled to obtain a uniformly mixed slurry, which specifically includes the following steps:

[0206] S101 weighs 38% A l 2 O 3 Nanocrystalline, 23% Si 3 N 4 Nanocrystalline, 15% Yb 2 O 3 Doped Y 2 O 3 The nano-crystals and 4% MgO nano-crystals were fed into a ball mill, and then the nano-ZrO 2 The ball is put into the ball mill, and the nano ZrO 2 The weight ratio of the balls to the feedstock is 10:1;

[0207] S102 was ball milled at 800 rpm for 6 hours under vacuum argon protection;

[0208] S103: adding a dispersant and a pore-forming agent, and continuing ball milling for 2 hours to obtain a uniformly mixed slurry, wherein the weight ratio of the dispersant to the pore-forming agent is 1:1;

[0209] S2 is to freeze-vacuum in-situ solidify the uniformly mixed slurry to obtain a porous ceramic pre-prestressed body, which specifically includes the following steps:

[0210] S201 injects the uniformly mixed slurry into a prefabricated mold and rapidly freezes it at -180°C to obtain a frozen slurry;

[0211] S202: transferring the frozen slurry to a vacuum in-situ curing device, curing and molding at -60°C for 23.5 hours to obtain a porous ceramic pre-prestressed body;

[0212] S3 sequentially supercritically dries and pre-sinters the porous ceramic pre-existing body to obtain an initial porous ceramic body, which specifically includes the following steps:

[0213] S301 supercritical drying includes the following steps: the porous ceramic pre-existing body is dried by supercritical CO 2 Drying to obtain a dried porous ceramic pre-fixed body;

[0214] S302 pre-sintering, including the following steps: pre-sintering the dried porous ceramic pre-preserved body at 800° C. for 2 hours to obtain an initial porous ceramic body;

[0215] S4 performs hot isostatic pressing sintering on the initial porous ceramic body to obtain a dense sintered carrier blank, which specifically includes the following steps:

[0216] S401: The initial porous ceramic body is placed in the hot pressing chamber of the hot pressing machine, and the vacuum degree in the hot pressing chamber is 10 -3 Pa, heated to 1600°C, applied uniaxial pressure of 100 MPa, and kept warm for 4 hours to prepare a dense sintered carrier blank;

[0217] S5 sequentially performs quantum control and high entropy infiltration on the dense sintered carrier blank to obtain a high entropy thermal quantum ceramic composite sintered carrier, which specifically includes the following steps:

[0218] S501 Quantum Control: Densely sintered carrier blanks are placed in a vacuum for 10 -3 In the Pa state, the temperature was kept at 900°C for 2 hours, the thermal oscillator was quantum controlled, and then cooled to 200°C to obtain a quantum controlled sintered carrier;

[0219] S502 High Entropy Infiltration: Infiltrate MgO nanopowder into the quantum controlled sintered carrier at 1800°C, cool it to room temperature, and obtain a high entropy thermal quantum ceramic composite sintered carrier.

[0220] Comparative Example 6

[0221] Comparative Example 6 provides a method for preparing a high entropy thermal quantized ceramic composite sintered carrier, comprising the following steps:

[0222] S1 weighs Al according to weight percentage 2 O 3 Nanocrystalline particles, Si 3 N 4 Nanocrystals, Yb 2 O 3 Doped Y 2 O 3 Nanocrystals, Y 2 Si 2 O 7 Doped Y 3 Al 5 O 12 The nano-crystals and MgO nano-crystals are ball-milled to obtain a uniformly mixed slurry, which specifically includes the following steps:

[0223] S101 weighs 38% Al according to weight percentage 2 O 3 Nanocrystalline, 23% Si 3 N 4 Nanocrystalline, 15% Yb 2 O 3 Doped Y 2 O 3 Nanocrystals and 20% Y 2 Si 2 O 7 Doped Y 3 Al 5 O 12 These nanoparticles are fed into a ball mill and then the nano ZrO 2 The ball is put into the ball mill, and the nano ZrO 2 The weight ratio of the balls to the feedstock is 10:1;

[0224] S102 was ball milled at 800 rpm for 6 hours under vacuum argon protection;

[0225] S103: adding a dispersant and a pore-forming agent, and continuing ball milling for 2 hours to obtain a uniformly mixed slurry, wherein the weight ratio of the dispersant to the pore-forming agent is 1:1;

[0226] S2 is to freeze-vacuum in-situ solidify the uniformly mixed slurry to obtain a porous ceramic pre-prestressed body, which specifically includes the following steps:

[0227] S201 injects the uniformly mixed slurry into a prefabricated mold and rapidly freezes it at -180°C to obtain a frozen slurry;

[0228] S202: transferring the frozen slurry to a vacuum in-situ curing device, curing and molding at -60°C for 23.5 hours to obtain a porous ceramic pre-prestressed body;

[0229] S3 sequentially performs supercritical drying and pre-sintering on the porous ceramic pre-existing body to obtain an initial porous ceramic body, which specifically includes the following steps:

[0230] S301 supercritical drying includes the following steps: the porous ceramic pre-existing body is dried by supercritical CO 2 Drying to obtain a dried porous ceramic pre-fixed body;

[0231] S302 pre-sintering, including the following steps: pre-sintering the dried porous ceramic pre-preserved body at 800° C. for 2 hours to obtain an initial porous ceramic body;

[0232] S4 performs hot isostatic pressing sintering on the initial porous ceramic body to obtain a dense sintered carrier blank, which specifically includes the following steps:

[0233] S401: The initial porous ceramic body is placed in the hot pressing chamber of the hot pressing machine, and the vacuum degree in the hot pressing chamber is 10 -3 Pa, heated to 1600°C, applied uniaxial pressure of 100 MPa, and kept warm for 4 hours to prepare a dense sintered carrier blank;

[0234] S5 sequentially performs quantum control and high entropy infiltration on the dense sintered carrier blank to obtain a high entropy thermal quantum ceramic composite sintered carrier, which specifically includes the following steps:

[0235] S501 Quantum Control: Densely sintered carrier blanks are placed in a vacuum for 10 -3 In the Pa state, the temperature was kept at 900°C for 2 hours, the thermal oscillator was quantum controlled, and then cooled to 200°C to obtain a quantum controlled sintered carrier;

[0236] S502 High Entropy Infiltration: Infiltrate MgO nanopowder into the quantum controlled sintered carrier at 1800°C, cool it to room temperature, and obtain a high entropy thermal quantum ceramic composite sintered carrier.

[0237] Experimental means of experimental data testing

[0238] The high entropy thermal quantized ceramic composite sintered carriers prepared in Examples 1-3 and Comparative Examples 1-6 were measured by the following experimental means:

[0239] 1. Thermal conductivity: The thermal diffusion coefficient is measured by a laser thermal conductivity analyzer (LFA467) produced by NETZSCH Instrument Manufacturing Co., Ltd. of Germany;

[0240] The thermal conductivity λ of the material is calculated by the measured thermal diffusion coefficient, and the calculation formula is as follows: λ = α·Cp·ρ. Among them, α represents the thermal diffusion coefficient of the ceramic material, Cp represents the specific heat capacity of the ceramic material, and ρ represents the actual density of the ceramic material;

[0241] Laser thermal conductivity analyzer LFA467 uses laser pulse method to measure thermal diffusion coefficient of ceramic materials: laser pulse flash point is performed on the surface of opaque dark sample without mirror reflection (light-colored samples need to be colored on the surface to avoid the reflection of the sample affecting the measurement accuracy); its principle is to emit laser to one side of the sample surface to radiate it, and the heat caused by radiation will spread to the other side of the sample. The thermal diffusion coefficient of the material is calculated by recording the time it takes for the temperature of the other side surface to rise to a certain set value. Three different thicknesses are selected for the same sample to measure (1.5mm, 2mm and 3mm respectively), and the average of the three measurements is taken as the measurement result;

[0242] 2. Density test: Use PEM density tester to test density, preload: 1.961N, main load weight: 10.58N, pressure needle size: 0.6mm, pressure depth 0.01mm, record instrument readings;

[0243] 3. Place the prepared sample on the support device of the three-point mechanical testing machine to ensure that the contact between the sample and the support point is smooth and firm;

[0244] Adjust the distance between the support points and determine the appropriate span according to the sample size and test requirements;

[0245] According to the test standard or experimental requirements, set the test machine's test speed, loading method and other parameters to ensure that the data recorded during the test is accurate and complete; start the test machine and gradually increase the load until the sample is damaged. During the load application process, pay attention to the deformation and damage characteristics of the sample; the test machine will automatically record the load-displacement data during the test. These data are the basis for the subsequent analysis of the sample's bending strength and deformation behavior;

[0246] According to the recorded load-displacement data, the three-point bending strength of the sample can be calculated. The calculation formula of the three-point bending strength is: σ = 3FL / (2bh), where F is the breaking load, L is the span, b is the sample width, and h is the sample height. The average value after three measurements is taken as the measurement result;

[0247] The experimental data of the high entropy thermal quantized ceramic composite sintered carriers prepared in Example 1 and Comparative Examples 1-6 measured by the above experimental means are shown in Table 1 below:

[0248] Table 1 Experimental data

[0249]

[0250] From Table 1, we can observe that the high entropy thermal quantized ceramic composite sintered carrier prepared in Examples 1-3 not only makes the thermal conductivity experimental data higher to solve the technical problem of poor thermal uniformity during high-temperature sintering, but also makes the density experimental data higher to solve the technical problem of poor density during high-temperature sintering, and at the same time makes the three-point bending strength experimental data higher to solve the technical problems such as the decrease in deformation resistance and anti-bursting rate during high-temperature sintering, thereby improving the performance and stability of the high entropy thermal quantized ceramic composite sintered carrier. The high entropy thermal quantized ceramic composite sintered carrier prepared in Comparative Documents 1-2 is different from that in Example 1 in terms of component content, especially Al 2 O 3 The content of nano-crystals in the ceramic composite sintered carrier is not controlled within the range of 35% to 45% by weight, resulting in a decrease in the thermal conductivity, density and three-point bending strength of the high entropy thermal quantized ceramic composite sintered carrier to varying degrees. Compared with Example 1, the high entropy thermal quantized ceramic composite sintered carrier prepared in Comparative Document 3 does not contain Al 2 O 3 Nano-grains, resulting in the largest decrease in the experimental data such as thermal conductivity, density and three-point bending strength of the high-entropy thermal quantized ceramic composite sintered carrier; the high-entropy thermal quantized ceramic composite sintered carrier prepared in Comparative Document 4 does not contain Yb 2 O 3 Doped Y 2 O 3 The nano-crystals of the high entropy thermal quantized ceramic composite sintered carrier result in a decrease in the experimental data such as the thermal conductivity, density and three-point bending strength. The high entropy thermal quantized ceramic composite sintered carrier prepared in Comparative Document 5 does not contain Y 2 S i 2 O 7 Doped Y 3 Al 5 O 12 The nano-crystals of the high-entropy thermal quantized ceramic composite sintered carrier result in a decrease in experimental data such as thermal conductivity, density and three-point bending strength. The high-entropy thermal quantized ceramic composite sintered carrier prepared in Comparative Document 6 does not contain MgO nano-crystals in its components compared to Example 1, which results in a decrease in experimental data such as thermal conductivity, density and three-point bending strength of the high-entropy thermal quantized ceramic composite sintered carrier.

[0251] It is to be understood that the present invention is described by some embodiments, and it is known to those skilled in the art that various changes or equivalent substitutions may be made to these features and embodiments without departing from the spirit and scope of the present invention. In addition, under the teachings of the present invention, these features and embodiments may be modified to adapt to specific circumstances and materials without departing from the spirit and scope of the present invention. Therefore, the present invention is not limited by the specific embodiments disclosed herein, and all various changes or equivalent substitutions falling within the scope of the claims of the present application are included. In addition, under the teachings of the present invention, these features and embodiments may be modified to adapt to specific circumstances and materials without departing from the spirit and scope of the present invention. Therefore, the present invention is not limited by the specific embodiments disclosed herein, and all embodiments falling within the scope of the claims of the present application are within the scope protected by the present invention.

Claims

1. A high entropy thermal quantum ceramic composite sintered carrier, characterized in that: The composition includes the following weight percentages: Al2O3 nanoparticles: 35% to 45%; Si3N4 nanocrystals: 20% to 30%; Yb2O3 doped with Y2O3 nanoparticles: 10% to 20%; Y2Si2O7 doped with Y3Al5O 12 Nano-grains: 15% to 25%; MgO nanocrystals: 2%~6%.

2. The high entropy thermal quantized ceramic composite sintered carrier according to claim 1, characterized in that: In the Yb2O3-doped Y2O3 nano-grains, the doping amount of Yb2O3 is 0.1% to 20%.

3. The high entropy thermal quantized ceramic composite sintered carrier according to claim 1, characterized in that: In the Y2Si2O7 doped with Y3Al5O 12 In the nano-grains, the doping amount of Y2Si2O7 is 10% to 50%.

4. The high entropy thermal quantized ceramic composite sintered carrier according to claim 1, characterized in that: The Al2O3 nano-crystals, the Si3N4 nano-crystals, the Yb2O3 nano-crystals doped with Y2O3, the Y2Si2O7 nano-crystals doped with Y3Al5O 12 The particle sizes of the nano-crystals and the MgO nano-crystals are 5 to 20 nm; the Al2O3 nano-crystals, the Si3N4 nano-crystals, the Yb2O3-doped Y2O3 nano-crystals, the Y2Si2O7-doped Y3Al5O 12 The specific surface area of ​​the nano-crystals and the MgO nano-crystals is >50m 2 / g.

5. A method for preparing a high entropy thermal quantum ceramic composite sintered carrier, characterized in that: The method of preparing the high entropy thermal quantized ceramic composite sintered carrier according to any one of claims 1 to 4 comprises the following steps: S1 weighed Al2O3 nanoparticles, Si3N4 nanoparticles, Yb2O3 doped Y2O3 nanoparticles, Y2Si2O7 doped Y3Al5O 12 The nano-crystals and MgO nano-crystals are ball-milled to obtain a uniformly mixed slurry; S2: performing in-situ freeze-vacuum solidification molding on the uniformly mixed slurry to obtain a porous ceramic pre-prestressed body; S3 sequentially supercritically drying and pre-sintering the porous ceramic preform to obtain an initial porous ceramic body; S4 hot isostatic pressing the initial porous ceramic body to obtain a dense sintered carrier blank; S5 sequentially performs quantum control and high entropy infiltration on the dense sintered carrier blank to obtain a high entropy thermal quantum ceramic composite sintered carrier.

6. The method for preparing the high entropy thermal quantum ceramic composite sintered carrier according to claim 5, characterized in that: In step S1, Al2O3 nanoparticles, Si3N4 nanoparticles, Yb2O3-doped Y2O3 nanoparticles, Y2Si2O7-doped Y3Al5O 12 The nano-crystals and MgO nano-crystals are ball-milled and mixed, which specifically includes the following steps: S101 weighs 35% to 45% Al2O3 nanoparticles, 20% to 30% Si3N4 nanoparticles, 10% to 20% Yb2O3 doped with Y2O3 nanoparticles, and 15% to 25% Y2Si2O7 doped with Y3Al5O 12 The nano-crystals and 2% to 6% MgO nano-crystals are fed into a ball mill, and then the nano-ZrO2 balls are put into the ball mill, wherein the weight ratio of the nano-ZrO2 balls to the feed is 10:1; S102 was ball milled at a speed of 750-850 rpm for 5-7 hours under vacuum argon protection; S103: adding dispersant and pore-forming agent, and continuing ball milling for 1.5 to 2.5 hours to obtain a uniformly mixed slurry, wherein the weight ratio of the dispersant to the pore-forming agent is 1:

1.

7. The method for preparing the high entropy thermal quantum ceramic composite sintered carrier according to claim 5, characterized in that: Step S2 is to freeze-vacuum in-situ solidify the mixed slurry, which specifically includes the following steps: S201 injects the uniformly mixed slurry into a prefabricated mold and rapidly freezes it at a temperature of -190 to -170°C to obtain a frozen slurry; S202: transferring the frozen slurry to a vacuum in-situ curing device, curing and molding at a temperature of -70 to -50°C for 23 to 24 hours to obtain a porous ceramic pre-prestressed body.

8. The method for preparing the high entropy thermal quantized ceramic composite sintered carrier according to claim 5, characterized in that: Step S3 sequentially performs supercritical drying and pre-sintering on the porous ceramic pre-existing body, which specifically includes the following steps: S301 supercritical drying, including the following steps: drying the porous ceramic pre-existing body by supercritical CO2 to obtain a dried porous ceramic pre-existing body; S302 pre-sintering includes the following steps: pre-sintering the dried porous ceramic pre-preserved body at a temperature of 750° C. to 850° C. for 1.5 to 2.5 hours to obtain an initial porous ceramic body.

9. The method for preparing a high entropy thermal quantum ceramic composite sintered carrier according to claim 5, characterized in that: Step S4 is to perform hot isostatic pressing sintering on the initial porous ceramic body, which specifically includes the following steps: S401: The initial porous ceramic body is placed in the hot pressing chamber of the hot pressing machine, and the vacuum degree in the hot pressing chamber is 10 -3 Pa, heated to 1500-1700° C., applied uniaxial pressure of 90-110 MPa, and kept warm for 3.5-4.5 hours to prepare a dense sintered carrier blank.

10. The method for preparing a high entropy thermal quantized ceramic composite sintered carrier according to claim 5, characterized in that: Step S5 sequentially performs quantum control and high entropy penetration on the dense sintered carrier blank, specifically comprising the following steps: S501 Quantum Control: Densely sintered carrier blanks are placed in a vacuum for 10 -3 In the Pa state, the temperature is kept at 850-950°C for 1.5-2.5 hours, the thermal oscillator is quantum controlled, and the temperature is cooled to 200°C to obtain a quantum controlled sintered carrier; S502 High Entropy Infiltration: Infiltrate MgO nanopowder into the quantum controlled sintered carrier at a temperature of 1800℃~2000℃, cool it to room temperature, and obtain a high entropy thermal quantum ceramic composite sintered carrier.

Citation Information

Patent Citations

  • Solidification preparation method for aluminum oxide-based ternary nanometer eutectic / amorphous ceramic

    CN107663081A

  • Alumina-based high-entropy eutectic ceramic and preparation method thereof

    CN113354398A

  • Y-Al-Si-O compact multiphase ceramic and preparation method thereof

    CN116425541A

  • Phosphor, wavelength conversion element, light source device and projector

    JP2018053227A

  • Plasma resistant ceramic body formed from multiple pieces

    US20230212082A1